2009
DOI: 10.1149/1.3071634
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Electrical Characteristics of Co-Germanide Contacts on Ge

Abstract: The microstructural evolution and corresponding electrical contact properties of Co-germanide systems were investigated. The Co-germanide formation process underwent several intermediate, high-resistive phases ͑CoGe and Co 5 Ge 7 ͒, while low-resistive CoGe 2 was formed over 650°C in a narrow process window of Ͻ100°C. Because of the strong Fermi level pinning effect, Co, CoGe, and Co 5 Ge 7 phases exhibited Schottky contact behaviors with similar Schottky barrier heights on n-type Ge and ohmic contact behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…[4,5,30] It has been reported that cobalt-doped germanium nanomaterials have low resistivity, high thermal stability, and room temperature ferromagnetism; this results in potential applications in effective on-chip interconnects and nanoelectrodes for highly integrated nanoelectronic devices, spintronic devices, and field-emission displays. [31][32][33][34][35][36] Investigating the structural and electronic properties of cobalt-doped germanium clusters may provide valuable information for developing cobalt/germanium materials, as well as their applications in electronic and magnetic materials. There have been several experimental and theoretical studies on cobalt-doped germanium clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5,30] It has been reported that cobalt-doped germanium nanomaterials have low resistivity, high thermal stability, and room temperature ferromagnetism; this results in potential applications in effective on-chip interconnects and nanoelectrodes for highly integrated nanoelectronic devices, spintronic devices, and field-emission displays. [31][32][33][34][35][36] Investigating the structural and electronic properties of cobalt-doped germanium clusters may provide valuable information for developing cobalt/germanium materials, as well as their applications in electronic and magnetic materials. There have been several experimental and theoretical studies on cobalt-doped germanium clusters.…”
Section: Introductionmentioning
confidence: 99%
“…In this configuration, 19a 1 , 20a 1 , 8b 1 , 14b 2 , and 5a 2 are predominantly 3d of Co, while 17a 1 , 18a 1 , and 7b 1 are mainly 4p orbitals of Ge 2 ligands. 3 A 1 and 3 A 2 are formed from 3 B 1 by moving one electron from 19a 1 and from 5a 2 to the 8b 1 orbital. At the RASPT2 level, 3 A 1 and 3 A 2 are computed to be just 0.06 and 0.15 eV above the ground state.…”
Section: Resultsmentioning
confidence: 99%
“…Cobalt-doped germanium clusters have attracted great attention of scientists because of their potential applications in electronic and magnetic materials. Investigation on the geometrical and electronic structures of cobalt-doped germanium clusters was performed with several experimental and theoretical methods. , Regarding the CoGe n –/0 ( n = 1–3) clusters, the structural, electronic, and magnetic properties of the neutral clusters were studied with density functional theory, but the spin states of these clusters were not reported. , Also, the photoelectron spectra of CoGe 2 – and CoGe 3 – clusters were measured with a photon energy of 266 nm . The anion spectra showed four bands at 1.96, 2.71, 3.33, and 3.60 eV for CoGe 2 – and four bands at 2.12, 2.66, 3.37, and 3.98 eV for the CoGe 3 – cluster.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental purpose of any photodetector is to convert optical signals into electrical signals, usually expressed as a photocurrent, which can be amplified, displayed and/or retransmitted. Ge has been attractive as an alternative substrate to Si because Ge has higher carrier mobility over Si and good compatibility with Si processing [3]. Due to its optical properties, Ge is a good candidate for the development of light detectors operating in the near infrared region (NIR: 800-1600 nm) especially when integration with Sibased devices are required.…”
Section: Introductionmentioning
confidence: 99%